A new taxonomy of the family Teloschistaceae. (6th March 2013) - Arup, Ulf; Søchting, Ulrik; Frödén, Patrik
<x xml:space="preserve">Abstract</x> The lichen family Teloschistaceae is one of the larger families of lichenized fungi. Currently it includes one very large heterogenous genus, Caloplaca, with some 1000 or more species with a vast variation in morphology, anatomy and chemistry. The rest of the family is split into 10–15 smaller genera, each with 20 or fewer species. There is no modern classification of the family based on molecular data. Here we attempt a first phylogenetic evaluation of a large part of the family, including a total of 337 species. Of these, 162 were used in a combined phylogenetic analysis of the ribosomal RNA sequence markers nrITS, nrLSU and mrSSU, using Bayesian inference. We also analysed all species using nrITS data, split into four different analyses. As a result we propose a new classification of the family, where a total of 39 genera are recognized, of which 31 are newly described or resurrected. The new genera are: Athallia, Austroplaca, Bryoplaca, Calogaya, Cerothallia, Flavoplaca, Gondwania, Haloplaca, Orientophila, Pachypeltis, Parvoplaca, Rufoplaca, Shackletonia, Scutaria, Sirenophila, Solitaria, Squamulea, Stellarangia, Teloschistopsis, Usnochroma, Variospora, Villophora and Wetmoreana. Resurrected genera are Blastenia, Dufourea, Follmannia, Gyalolechia, Leproplaca, Polycauliona, Pyrenodesmia and Xanthocarpia. The species Orientophila subscopularis is described as new. A third subfamily, Teloschistoideae, is proposed to accommodate the genus Teloschistes and related genera, parallel to the two previously recognized subfamilies Xanthorioideae and Caloplacoideae. We also show the large plasticity in both morphological and anatomical characters between closely related species within genera, indicating the low value of these as evolutionary markers. The secondary chemistry is a better marker in some parts of the family. We recognize a large number of geographically delimited clades with clear centres of evolution, but often showing large variation in morphology and anatomy.